Repositioning the efficiency of DFIs in a classical emerging market: The Case of South Africa - Mopeli, Kgotso Kenneth (Graduate School of Business (GSB), 2019)
The research study investigated the roles and challenges of DFIs in stimulating economic growth in an emerging market using DBSA and IDC, South Africa as a case study. The research study used a convergent mixed method research in understanding various intricacies surrounding challenges faced by the DFIs, by combining primary data obtained through a propulsive sampling of executive managers, senior managers and heads of divisions in a sample size of seven respondents for the qualitative analysis and quantitative secondary data obtained from annual reports and annual financial statements of both DBSA and IDC spanning five years. Moreover, the research study identified the role of DFIs in national economic policy formation and challenges hindering DFIs from meeting their mandates using qualitative analytical method of discourse and narrative analysis. Development banks across the globe play a sacrosanct role in stimulating economic development and economic growth in their respective jurisdictions. South Africa has various DFIs involved in different sectors of the economy. The country has seen minimal economic growth in recent years, and this is evidenced by the GDP growth rate, inequality and high unemployment rate. The research study findings revealed that the level of South African DFIs contribution to the total GDP value of the country is incredibly low when benchmarked against other emerging markets DFIs contribution to their countries’ GDP. The study also found that there is less participation on the side of the DFIs in policy-formulation. Moreover, the research findings further discovered that some of the targets entrenched in the economic policy frameworks guiding these institutions are impossible to achieve, let alone realise, rendering some of the targets as nothing but sheer chimera. The failure of other major state-owned entities places added responsibilities on these DFIs thus causing an overlap in their policy mandates. DFIs are faced with a conundrum of extending long term financing whilst remaining financially sustainable in the long run. Unlike many state-owned development banks from around the world, South African DFIs lack development capital from the government. While South African DFIs are active, well run and profitable, regrettably however their investments have not translated into meaningful economic development and this research study investigates why.